2012
DOI: 10.1039/c2cp41094j
|View full text |Cite
|
Sign up to set email alerts
|

The structure of 5-cyanoindole in the ground and the lowest electronically excited singlet states, deduced from rotationally resolved electronic spectroscopy and ab initio theory

Abstract: The structure and electronic properties of the electronic ground and the lowest excited singlet states of 5-cyanoindole (5CI) were determined using rotationally resolved spectroscopy of the vibrationless electronic origin of 5CI. In contrast to most other indole derivatives, the lowest excited state of 5CI is determined to be of L(a) character. The conventional approximate coupled cluster singles and doubles model (CC2) fails to describe the geometry of the excited state correctly. Nevertheless, scaling the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 34 publications
3
44
1
Order By: Relevance
“…Therefore, by investigating the photophysical properties of these cyanoindoles, we hope to identify an indole derivative that could be used to investigate these bacterial processes via fluorescence spectroscopy and/or microscopy, provided that the corresponding CN substitution does not significantly alter the biological activity in question. (3) One of these CNI derivatives (i.e., 5-CNI) has become a popular model in recent theoretical and computational interrogations of how a simple substitution affects the electronic structures and energetics of the indole ring [13–18]. In this regard, we believe that the photophysical results obtained from our study will not only provide new experimental results for comparison but can also be used to benchmark various quantum mechanical calculation methods.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Therefore, by investigating the photophysical properties of these cyanoindoles, we hope to identify an indole derivative that could be used to investigate these bacterial processes via fluorescence spectroscopy and/or microscopy, provided that the corresponding CN substitution does not significantly alter the biological activity in question. (3) One of these CNI derivatives (i.e., 5-CNI) has become a popular model in recent theoretical and computational interrogations of how a simple substitution affects the electronic structures and energetics of the indole ring [13–18]. In this regard, we believe that the photophysical results obtained from our study will not only provide new experimental results for comparison but can also be used to benchmark various quantum mechanical calculation methods.…”
Section: Introductionmentioning
confidence: 77%
“…4), the results obtained with 6-CNI show a similar linear correlation when those obtained in H 2 O and TFE are excluded. Previous studies have shown that, upon transition to the first electronic excited state, a partial negative/positive charge will be accumulated at the CN/NH group of 5-CNI [13, 18], which, in turn, will increase the H-bonding interactions between these sites and solvent having non-zero β and/or α values. Therefore, it is not surprising that a solvent’s H-bonding ability (as measured by β and α ) will play a role in the excited-state decay kinetics of 5-CNI.…”
Section: Resultsmentioning
confidence: 99%
“…However, it might be of interest that in some cases the SCS approximation is necessary to obtain the right order of states. 90 Because oB97XD is considerably less demanding than SCS-CC2 or SCS-ADC(2) we were able to compute larger clusters e.g. trimers and tetramers of PTCDA.…”
Section: Technical Detailsmentioning
confidence: 98%
“…In spectroscopy, the nitrile group is an excellent infrared (IR) sensitizer in revealing its local conformational landscape because the C N stretching vibration is strongly affected by its immediate local environment [2]. Among the numerous experimental and theoretical studies of the C N stretching vibration of nitrile-containing molecules [2][3][4][5][6][7][8][9][10][11][12] 5-cyanoindole (5CI) has recently been studied by experiment [11] and theory [2]. Schmitt and coworkers studied the electronic properties of 5CI using rotationally resolved spectroscopy and compared them with the results of ab initio calculations [11].…”
Section: Introductionmentioning
confidence: 99%
“…Among the numerous experimental and theoretical studies of the C N stretching vibration of nitrile-containing molecules [2][3][4][5][6][7][8][9][10][11][12] 5-cyanoindole (5CI) has recently been studied by experiment [11] and theory [2]. Schmitt and coworkers studied the electronic properties of 5CI using rotationally resolved spectroscopy and compared them with the results of ab initio calculations [11]. Using molecular dynamics simulations, Waegele and Gai have demonstrated the hydration-induced spectral broadening of the C N vibration of 5CI [2].…”
Section: Introductionmentioning
confidence: 99%